ANALISIS PENGARUH ROE, DER, TATO, CAPEX DAN NCCR TERHADAP HARGA SAHAM (Studi Kasus pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang terdaftar di Bursa Efek Indonesia Periode 2010-2014) - Cathelia, Nadia; Sampurno, R. Djoko (Diponegoro Journal of Management, 2016)
The intense competition in business and economy that happened now is one of the causes for the company’s mangement to improve their best performance to attract the investors to invest in their company. Basically, stock price is a reference for the investors to make investment decisions. Stock prices always fluctuate depend to the level of market’s supplies and demands. The stock price is influenced by several factors, internal and external factors. Internal factors can be seen from the company’s financial statements through the financial ratios such as ROE, DER, TATO, CAPEX and NCCR. This study aims to determine the effect of ROE, DER, TATO, CAPEX and NCCR toward the stock price.Population and samples in this study are all manufacturing companies, consumer goods industry sector listed on the Stock Exchange of the year 2010-2014. Purposive sampling methods of sampling and obtained a sample of 24 companies. Type of data is secondary. Multiple linear regression is used to determine the effect of ROE, DER, TATO, CAPEX and NCCR toward the stock price.The results showed that ROE have significant and positive effect toward the stock price meanwhile DER have significant and negative effect toward the stock price. Simultaneously test results indicate there is influence between ROE, DER, TATO, CAPEX and NCCR together toward the stock price of all manufacturing companies, consumer goods industry sector listed on the Stock Exchange. The magnitude of the effect was 42,7%, while the remaining 57,3% influenced by other factors outside this research.